STRATEGIC CAPABILITIES AND EXPORT PERFORMANCE OF MANUFACTURING SME IN MALAYSIA - Siti Normah Awang Tuah; Noor Hazlina Ahmad; Hasliza Abd Halim (International Journal of Accounting, Finance and Business, 2021)
Research on export performance among SMEs in Malaysia has become moresignificant nowadays as export is a major source of income for most countries. It is importantfor SMEs especially those in emerging countries like Malaysia to look into and put their effortsto strategize their capabilities to respond to the global competition and business opportunitiesin enhancing their export performance. Thus, this study was conducted to examine the currentSMEs capabilities before they adopt the best strategic approach to face challenge situations athand to enhance their export performance. A quantitative approach was employed in this studyand a total of 187 responses from manufacturing SME exporters were received and furtheranalysed using Partial Least Square (PLS) technique. The results demonstrated that somestrategic capabilities give significant impact but some are not towards the export performancein Malaysia.